A Regional View of the Response to Climate Change: A Meta-Analysis of European Benthic Organisms’ Responses - Hoppit, George; Schmidt, Daniela N. (Frontiers in Marine Science, 2022)
Climate change is impacting organisms in every region of the world ocean by acting though on individuals in response to their local environments. Given projected future risks derived from these changes, it is becoming increasingly important to understand regional signals of how organisms respond to facilitate their governance and protection. Benthic organisms structure ecological compositions and ecosystem dynamics, therefore not only providing insights into their own response to climate change but also how ecosystems might respond to future conditions. European seas are transitional areas including boreal, warm-temperate, and subarctic waters with organisms frequently at limits of their distributions. Here, we use a meta-analytical approach to assess how calcification, growth, metabolism, photosynthesis, reproduction, and survival in European benthic organisms respond to ocean acidification and warming. Using meta-regression, we examine how study design factors influence effect-size outcomes. Longer experimental periods generally amplified the effects of climate change on taxonomic groupings and related physiological traits and against expectation do not result in acclimation. In agreement with global studies, we find that impacts vary considerably on different taxonomic groupings and their physiological traits. We found calcifying organisms are an at-risk taxon in European waters, with climate stressors decreasing growth rates, reproduction, and survival rates. Fleshy algal species demonstrate resilience to climate stressors, suggesting future European benthic ecosystems will undergo restructuring based on current climate emission pathways.